RAPID-CRISPR: highly sensitive diagnostic assay for detection of PML::RARA isoforms in acute promyelocytic leukemia - Maity, Akash; Sathyanarayanan, Amritha; Kumar, Rohit; Vora, Jesal; Gawde, Jitendra; Jain, Hasmukh; Bagal, Bhausaheb; Subramanian, P. G.; Sengar, Manju; Khattry, Navin; Patkar, Nikhil; Hasan, Syed K. (Blood advances, 2025)
Acute promyelocytic leukemia (APL), distinguished by the presence of PML::RARA fusion transcript, is a medical emergency because of its high early death rate, which is preventable when diagnosed early. Current diagnostic methods are precise and reliable but are time intensive, require sophisticated instruments, and analytical expertise. This study has redefined APL identification by CRISPR system (RAPID-CRISPR) to rapidly (<3 hours) detect PML::RARA. APL cell lines (NB4 and UF-1) and bone marrow/peripheral blood samples from 74 patients with APL (66/8, retrospective/prospective) and 48 controls were included in the study. We used a DETECTR (DNA endonuclease-targeted CRISPR transreporter) assay to identify the bcr1, bcr2, and bcr3 PML::RARA isoforms. To ensure high specificity, we used PML::RARA-specific loop-mediated isothermal amplification (LAMP) primers, synthetic protospacer-adjacent motif sites, and isoform-specific CRISPR RNAs. RAPID-CRISPR recognized APL with 100% sensitivity and 100% specificity in an ambispective cohort of patient samples. Furthermore, our blinded validation approach to detect PML::RARA in an unbiased manner provides an additional layer in the diagnostic precision of APL. RAPID-CRISPR demonstrated superior sensitivity, detecting as few as 1 copy of PML::RARA compared with 10 copies by the gold-standard reverse transcriptase qualitative and quantitative polymerase chain reaction. The nucleic acid extraction-free protocol combined with the 1-step reverse transcriptase LAMP-based DETECTR followed by lateral flow readout makes the RAPID-CRISPR assay suitable for diagnosing APL in point-of-care settings. This simple, cost-effective tool, with its easy-to-read format, is particularly valuable in underresourced regions. The assay facilitates timely diagnosis and prompt administration of lifesaving therapies such as all-trans retinoic acid and arsenic trioxide in APL.
Online veröffentlicht: 29. Januar 2025
Gesehen am 15.07.2025